State intervention, South-South cooperation and structural transformation: the (ignored) case of Brazil-Venezuela cooperation for equity of access to university education, 2003-2016 - Muhr, Thomas (Revista Eletrônica de Educação, 2019)
This article re-visits Brazil-Venezuela official cooperation in the period 2003-2016, during which state interventionist policies improved social and educational justice. By drawing from an education governance approach, a pluriscalar analysis of equity of access to university education is conducted, which integrates an account of distributional justice in access to university education in Brazil and Venezuela with a structural approach related to South–South cooperation (SSC) among the two nations as well as within the Southern Common Market (MERCOSUR). Two interrelated arguments are developed: first, despite persistent inequities in access to university education in both territories, state-interventionist policies enhanced equity of access directly with respect to availability and accessibility. Second, the case of the Brazil/Venezuela Régimen Especial Fronterizo illustrates that SSC can transform the background conditions for educational justice by producing an alternative structure to the neoliberal global governance of education. Empirically, the discussion draws from contents and discourse analysis of 81 cooperation documents signed among Brazilian and Venezuelan state and non-state actors, complemented by municipal, national and regional development plans and commission reports, and 1 month of field research in the Régimen Especial Fronterizo in 2012. Participant observation and 13 semi-structured, open-ended interviews were conducted with officials at different levels of the policymaking processes, academics, as well as local scale actors in distinct cooperation and integration initiatives on both sides of the Brazil/Venezuela border. Resumo Este artigo revisita a cooperação oficial Brasil-Venezuela no período 2003-2016, durante o qual as políticas intervencionistas estaduais aprimoraram a justiça social e educacional. Partindo de uma abordagem de governança educacional, é realizada uma análise pluriescalar da equidade de acesso ao ensino universitário, que integra um relato de justiça distributiva no acesso ao ensino universitário no Brasil e na Venezuela com uma abordagem estrutural relacionada à cooperação Sul-Sul (CSS) entre as duas nações e também dentro do Mercado Comum do Sul (MERCOSUL). Dois argumentos inter-relacionados são desenvolvidos: primeiro, apesar das persistentes desigualdades no acesso à educação universitária em ambos os territórios, as políticas estatais intervencionistas aumentaram a igualdade de acesso diretamente em relação à disponibilidade e acessibilidade. Em segundo lugar, o caso do Régimen Especial Fronterizo Brasil / Venezuela ilustra que a CSS pode transformar as condições de fundo para a justiça educacional, produzindo uma estrutura alternativa à governança global neoliberal da educação. Empiricamente, a discussão recorre à análise de conteúdo e discurso de 81 documentos de cooperação assinados entre atores estatais e não-estatais brasileiros e venezuelanos, complementados por planos de desenvolvimento e relatórios de comissões municipais, nacionais e regionais, e 1 mês de pesquisa de campo no Régimen Especial Fronterizo em 2012. A observação participante e 13 entrevistas semi-estruturadas e abertas foram conduzidas com funcionários em diferentes níveis dos processos de formulação de políticas, acadêmicos, bem como atores de escala local em diferentes iniciativas de cooperação e integração em ambos os lados da fronteira Brasil / Venezuela. Keywords: Brazil/Venezuela international cooperation, Education governance, Education policy, Equity in higher education. Palavras-chave: Brasil/Venezuela cooperação internacional, Governança da educação, Política educacional, Equidade na educação superior. References ABBOTT, A. Of time and space: The contemporary relevance of the Chicago School. Social Forces, 75(4), 1149–1182, 1997. APORREA. Presidente Maduro inaugura Universidad Martin Luther King en el estado Lara, www.aporrea.org/educacion/n323129.html, 2018. APORREA. Presidente Maduro aprueba 16 mil 557 millones de bolívares para el Plan Ofensiva Comunal, www.aporrea.org/misiones/n341217.html, 2019. AZEVEDO, M. L. N. (2015a). Transnacionalização e mercadorização da educação superior: Examinando alguns efeitos colaterais do capitalismo acadêmico (sem riscos) no Brasil—a expansão privado-mercantil. Revista Internacional de Educação Superior, 1(1), 86–102. AZEVEDO, M. L. N. (2015b). Higher education and international organizations: Cold War, commodification, and the global field of power. In S. Tuleski (Ed.), Liberation psychology in Brazil (pp. 13–39). New York: Nova. CABRERA, A. (2009). Construcción del conocimiento desde la comunicación. Intercultural. experiencias en el proceso pedagógico desarrollado en la aldea indígena. Kamarata. Paper presented at the XXVII Congreso de la Asociación Latinoamericana de Sociología. Asociación Latinoamericana de Sociología, Buenos Aires, 2009. http://www.aacademica.com/000-062/2272. Accessed September 6, 2015. CIA (2019) World Fact Book, https://www.cia.gov/library/publications/the-world-factbook/geos/br.html (accessed 24 May 2019). DALE, R. The state and the governance of education: An analysis of the restructuring of the state-education relationship. In A. H. Halsey, H. Lauder, P. Brown, & A. S. Wells (Eds.), Education. Culture, economy, society (pp. 273–282). Oxford: Oxford University Press, 1997. DALE, R. Globalisation, knowledge economy and comparative education. Comparative Education, 41(2), 117–149, 2005. SANTOS, S.A.D. Affirmative action and political dispute in today’s Brazilian academe. Latin American Perspectives, 41(5), 141–156, 2014. DUFFY, M. Education, democracy and social change: Venezuela’s education missions in theory and practice. Journal of Education Policy, 30(5), 650–670, 2014. FERRARO, D. Políticas e iniciativas en MERCOSUR en el ámbito de la integración fronteriza, SP/XXIV-RDCIALC/Di No. 14-13. Caracas: SELA, 2013. GOLDSTEIN, A.A. The New Far-Right in Brazil and the Construction of a Right-Wing Order. Latin American Perspectives, 2019, https://doi.org/10.1177/0094582X19846900 GOMES, A. M.; ROBERTSON, S. L.; DALE, R. Globalizing and regionalizing higher education in Latin America. In D. Araya & P. Marber (Eds.), Higher education in the global age. Policy, practice and promise in emerging societies (pp. 160–183). London: Routledge, 2014. GRIFFITHS, T. Higher education for socialism in Venezuela: Massification, development and transformation. In T. G. Griffiths & Z. Millei (Eds.), Logics of socialist education: Engaging with crisis, insecurity and uncertainty (pp. 91–112). London: Springer, 2013. INEP. (2013). Censo da educação superior 2013. Instituto Nacional de Estudos e Pesquisas Educacionais. http://download.inep.gov.br/educacao_superior/censo_superior/apresentacao/2014/coletiva_censo_superior_2013.pdf. Accessed September 8, 2015. IINSTITUTO SOCIAL DEL MERCOSUR. (2015). Economía social y solidaria—resumen. http://ismercosur.org/proyectos/economia-social-y-solidaria/. Accessed June 2, 2014. LANGTHALER, M. (forthcoming). Education Policies and Counter-hegemony in Bolivarian Venezuela. Vienna: Praesens VerlagesmbH. LARSEN, M.A.; BEECH, J. Spatial Theorizing in Comparative and International Education Research. Comparative Education Review, Vol. 58, No. 2 (May 2014), pp. 191-214, 2014. LEAL, F.G. Walking toward the cliff. Inside Higher Ed, 19 May 2019, https://www.insidehighered.com/blogs/world-view/walking-toward-cliff. MANSFIELD, B. (2005). Beyond rescaling: Reintegrating the ‘national’ as a dimension of scalar relations. Progress in Human Geography, 29(4), 458–473. MARSTON, S. A.; SMITH, N. States, scales and households: Limits to scale thinking? A response to Brenner. Progress in Human Geography, 25(4), 615–619, 2001. MARTIN, G. Scaling critical pedagogy in higher education, Critical Studies in Education, Vol. 58, No. 1, 1–18, 2017. MARTINEZ, M. V. Redes urbanas transfronterizas: Dos escenarios venezolanos. Aldea Mundo. Revista sobre Fronteras e Integración, 14(27), 7–15, 2009. MCCOWAN, T. Expansion without equity: An analysis of current policy on access to higher education in Brazil. Higher Education, 53(5), 579–598, 2007. MCCOWAN, T. Three dimensions of equity of access to higher education. Compare: A Journal of Comparative and International Education, 45(5), 792–813, 2015. MERCOSUR. (2000). Plan estratégico 2001–2005. http://www.sic.inep.gov.br/es-ES/documentoscategoria/finish/7-planos-planes/411-plano-2001-2005.html. MERCOSUR. (2005). Plan del sector educativo del MERCOSUR 2006–2010. http://www.sic.inep.gov.br/es-ES/documentos-categoria/finish/7-planos-planes/412-plano-2006-2010.html. MERCOSUR. (2006). Declaración final. Brasilia, 14 December. MERCOSUR. (2007). XXXII Reunión de ministros de educación de los países del MERCOSUR. MERCOSUR/XXXII RME/ACTA No. 01/07, 1 June. MERCOSUR. (2011). Plan de acción del sector educativo del MERCOSUR 2011–2015. http://www.sic.inep.gov.br/es-ES/component/jdownloads/finish/7/414.html. MERCOSUR. (2012a). Plan estratégico de acción social. Asunción: Instituto Social del MERCOSUR. MERCOSUR. (2012b). Comunicado conjunto de los presidentes de los estados partes del MERCOSUR. Mendoza, 29 June. MERCOSUR. (2012c). Comunicado conjunto de los presidentes de los estados partes del MERCOSUR. Brasilia, 7 December. MERCOSUR. (2017) Suspensión de Venezuela en el MERCOSUR, https://www.mercosur.int/suspension-de-venezuela-en-el-mercosur/ MINCI. (2004). Desarrollo endógeno. Desde adentro, desde la Venezuela profunda. Caracas: Ministerio de Comunicación e Información. MPPEU. (2012). Logros de la educación universitaria 2012. Caracas: Ministerio del Poder Popular para la Educación Universitaria. MPPEU. (2015). Memoria y cuenta. Caracas: Ministerio del Poder Popular para la Educacioón Universitaria. MPPEU. (2016). Memoria 2015. Caracas: Ministerio del Poder Popular para la Educación Universitaria. MUHR, T. (2010). Venezuela e ALBA: Regionalismo contra-hegemónico e ensino superior para todos, Educação e Pesquisa, 36(2): 611-27. DOI:10.1590/S1517-97022010000200013 MUHR, T. (2011). Venezuela and the ALBA: Counter-hegemony, geographies of integration and development, and higher education for all. Saarbrücken: VDM. MUHR, T. (2016). South-South development cooperation and the socio-spatial reconfiguration of Latin America-Caribbean regionalisms: University education in the Brazil-Venezuela ‘Special Border Regime’. In S. L. Robertson, K. Olds, R. Dale, & Q. A. Dang (Eds.), Global regionalisms and higher education: Projects, processes, politics. Cheltenham: Edward Elgar. MUHR, T. (2017) South–South Cooperation and the Geographies of Latin America– Caribbean Integration and Development: A Socio-Spatial Approach. Antipode, 49(4): 843-866. MUHR, T. (2019). Geographies of South-South relations and regionalisation processes in Latin America-Caribbean. In E. Fiddian-Qasmiyeh & P. Daley (eds) The Handbook of South-South Relations, pp. 95-111. London: Routledge. MUHR, T.; AZEVEDO, M.L.N. (2019). Relações Sul-Sul em Educação: o programa ¡Yo, Sí Puedo! e a cooperação em educação do BRICS em foco. Revista Ibero-Americana de Estudos em Educação, 14(1): 2-30. DOI:10.21723/riaee.v14i1.11730. MUHR, T.; VERGER, A. (2006). Venezuela: Higher education for all. The Journal for Critical Education Policy Studies, 4(1), 160–194. OPSU. (2015). Sistema Nacional de Ingreso. Oficina de Planificación del Sector Universitario. http://ingreso.opsu.gob.ve/. Accessed September 6, 2015. PRESIDÊNCIA DA REPÚBLICA. Decreto no. 4.793, 23 July, 2003. PRESIDÊNCIA DA REPÚBLICA. Lei no. 11.096, 13 January, 2005. PRESIDÊNCIA DA REPÚBLICA. Decree no. 6.047, 22 February, 2007. PRESIDÊNCIA DA REPÚBLICA. Lei no. 12.711, 29 August, 2012. PRESIDÊNCIA DA REPÚBLICA. Lei no. 13.005, 25 June, 2014. RBV. Líneas generales del plan de desarrollo económico y social de la nación, 2001–2007. Caracas: RBV, 2001. RBV. Líneas generales del plan de desarrollo económico y social de la nación, 2007–2013. Caracas: RBV, 2007. RBV. Venezuela: Modelo exitoso de inclusion. Caracas: RBV, 2017 RBV. Plan de la Patria 2025. Caracas: RBV, 2019. RBV/RFB. Comunicado conjunto: Alianza estratégica Venezuela–Brasil. Caracas, 14 February 2005. RBV/RFB. Comunicado conjunto. Recife, 26 March, 2008a. RBV/RFB. Memorando de entendimiento entre el Ministerio del Poder Popular para la Educación Superior de la República Bolivariana de Venezuela (MPPES) y el Ministerio de Educación de la República Federativa de Brasil. Recife, 26 March 2008b. RBV/RFB (2008c). Entendimiento entre el Ministerio del Poder Popular para la Educación Superior de la República Bolivariana de Venezuela (MPPES) y la Fundación de Perfeccionamiento de Personal de Nivel Superior de la República Federativa de Brasil (CAPES). Recife, 26 March. RBV/RFB (2008d). Comunicado conjunto. Recife, 27 March. RBV/RFB (2008e). Comunicado conjunto. Caracas, 27 June. RBV/RFB (2009). Comunicado conjunto de los presidentes Hugo Chávez Frías y Luiz Inácio Lula da Silva, en ocasión del encuentro presidencial realizado en el Proyecto Agrario Socialista Plancie de Maracaibo. Maracaibo, 16 January. RBV/RFB (2010a). Acuerdo entre el gobierno de la República Bolivariana de Venezuela y el gobierno de la República Federativa del Brasil sobre localidades fronterizas vinculadas. Brasilia, 28 April. RBV/RFB (2010b). Acuerdo entre el gobierno de la República Bolivariana de Venezuela y el gobierno de la República Federativa del Brasil para el establecimiento de un régimen especial fronterizo. Caracas, 6 August. RBV/RFB (2014). IX reunión bilateral Brasil-Venezuela de los organismos nacionales competentes para la aplicación del acuerdo de transporte internacional por carretera de pasajeros y carga. Santa Elena de Uairén, 25/26 March. RFB (2007a). Política nacional de desenvolvimento regional (sumário executivo). Brasilia: Ministério da Integração Nacional. RFB (2007b). The plan for the development of education. Reasons, principles and programs. Brasilia: Ministerio da Educação. ROBERTSON, S.; DALE, R. The social justice implications of privatisation in education governance frameworks: A relational account. Oxford Review of Education, 34(9), 426–445, 2013. SOBRINHO, J. D.; BRITO, M. R. F. Higher education in Brazil: Main trends and challenges. In F. L. Segrera, C. Brock, & J. D. Sobrinho (Eds.), Higher education in Latin America and the Caribbean 2008 (pp. 235–253). Caracas: UNESCO/IESALC, 2009. SWYNGEDOUW, E. Neither global nor local: “glocalization” and the politics of scale. In K. R. Cox (Ed.), Spaces of globalization. Reasserting the power of the local (pp. 137–166). New York: Guildford, 1997. TELESUR (2019) Brazil: Hundreds of thousands of teachers, students strike in protest against Bolsonaro’s policies, https://www.telesurenglish.net/multimedia/Brazil-Hundreds-of-Thousands-of-Teachers-Students-Strike-in-Protest-Against-Bolsonaros-Policies-20190515-0012.html TORO, L. F. La aldea universitaria bolivariana. Paginadigital, 29 October 2004, http://www.paginadigital.com.ar/articulos/2004/2004cuart/educacion/e1422610-4.asp. Accessed October 2, 2015. UIS. Global education digest 2010. Montreal: UNESCO Institute for Statistics, 2010. UIS. Statistical tables. Education: Gross enrolment ratio by level of education. http://data.uis.unesco.org/index.aspx?queryid=142&lang=en. Accessed September 5, 2015. UIS. Venezuela, http://uis.unesco.org/en/country/ve. Accessed May 26, 2019. WEISBROT, M.; SACHS, W. Economic Sanctions as Collective Punishment: The Case of Venezuela. Washington: Center for Economic and Policy Research, 2019, http://cepr.net/images/stories/reports/venezuela-sanctions-2019-04.pdf